Traffic Circulation Efficiency of Elliptical Roundabouts - Fathullah, Hardi S.; Majid, Hirsh M.; Ahmed, Chro H.; Sourkan, Sulleyman H.; Ismael, Karzan S.; Abdulsamad, Balen Z. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
This paper investigates the impact of geometry of central island of roundabout on operational performance in terms of delay and capacity measures. A roundabout with an elliptical central island having major and minor axes of 63 and 44m respectively was selected as a case study. Using SIDRA Intersection software two simulation models are developed while considering two geometric shapes of central island; one with an elliptical shape and the other with a circular shape. The peak traffic volume of each approach was assigned to both models as a preliminary simulation then twelve scenarios were generated by assigning identical lane volumes starting from a value that gave level of service A and increasing gradually to level of service F. In each scenario 100% of the volume assigned to an approach while the other was assigned with 75% of it and this process was reversed for every run. The results revealed that at high degree of saturation, the elliptical roundabout generally possessed a higher performance especially in term of delay and capacity compared to the circular roundabout. Furthermore, a parametric study was carried out through running eight more simulation scenarios to examine the impacts of heavy vehicle percentage (HV%) on the roundabout operational performance. The (HV %) started from 2% and increased to 12% with alternate approach virtual volume, and the results showed that performance of the elliptical roundabout was higher than the circular roundabout. However it was more susceptible to increase of HV% in term of control delay and capacity.